Can the Amiable Compositeur System Be the Support Needed by the Public Attorney to Settle Disputes and Not Submit them to Arbitration? - Talavera Cano, Andrés (2015)
It is known the case of the public attorneys that, having the opportunity to settle a controversy aroused between the public entity and the contractor, prefer to submit that dispute to arbitration with higher costs that this decision cause to the State. The reason? The concern of having «the reasonableness of his decision to settle the dispute» subjected to an administrative responsibility procedure.This paper aims to discuss this problem and analyze a possible solution. Thus, taking into consideration the Colombian experience and the recent Peruvian regulation in the «Reglamento de la Ley de APPs», the authors suggest to include in the «Nueva Ley de Contrataciones del Estado» the «Amicable Compositor» as a mechanism of alternative dispute resolution.